PENGUJIAN CAR DAN BOPO SEBAGAI MEDIASI DALAM MENILAI KINERJA KEUANGAN (STUDI KASUS BANK UMUM SYARIAH DI INDONESIA) - Akbar, Dinul Alfian (Balance : Jurnal Akuntansi dan Bisnis, 2016)
ABSTRACTIn carrying out the function of intermediation, the bank dealing with the risks stemming from one of the main activities of banks that fund distribution activities in the form of credit. The purpose of this study to determine the effect on ROA NPF, mediated CAR and ROA in banks in Indonesia in 2010-2014.The sampling method used was purposive sampling which resulted in a total sample of six Islamic Banks and population in this study were 12 Islamic Banks registered in Indonesian banks.By using path analysis results of the study found the NPF as a proxy for risk financing negatively affect profitability ROA that is a proxy. NPF also negatively affect the CAR that is a proxy of capital adequacy and do not affect the BOPO that is a proxy of operational efficiency. CAR mediates the effect of NPF to ROA. While BOPO not mediate the effect of NPF to ROA.